Gen Z's Motivation and Challenges in Blitar for Running Family Business - Septiawan, Bambang; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explore the motivations of Generation Z in Blitar in running a family business. Using a qualitative approach, data were collected through in-depth interviews with 25 respondents involved in family businesses. The results showed that their main motivations included responsibility for family tradition and heritage, the desire to achieve financial independence, and self-development. Despite significant challenges such as financial difficulties and competition, respondents showed resilience and innovation in overcoming obstacles. The strategies implemented included product innovation, digital marketing, and good financial management. These findings provide important insights into the role of Gen Z in family businesses and their implications for local economic development, as well as highlighting the need for support for entrepreneurship education and access to financial resources.